Принципи права: окремі онтологічні, гносеологічні та аксіологічні проблеми - Богініч, О.Л. (Альманах права, 2012)
У статті досліджується ґенеза принципів права, їх взаємозв’язок з атрибутивними властивостями права та їх цінність для суспільства. Пропонуються заходи з підвищення ефективності функціонування правових систем на базі вдосконалення механізмів дії правових принципів. В статье исследуется генезис принципов права, их взаимосвязь с атрибутивними свойствами права и их ценность для общества. Предлагаются меры по повышению эффективности функционирования правових систем на базе усовершенствования механизмов действия правовых принципов. The article examines the genesis of the legal principles, their interaction with the attribute properties of the law and society values. As an example, the thesis that the legal principles are the category that has historical content proves by such principles like legal equality, freedom, justice etc. The principle of legal equality is seen to be a fundamental principle, which is associated with the existence of such legal principles as freedom and justice. It is shown that the implementation of legal equality principle in transitional societies leads to social stratification as more active individuals (mostly due to the use of unjust means to achieve their goals), take higher level of social hierarchy. State in this regard does not perform its functions guarantor of the public interest because she is the personification of the benefits of such individuals in the political sphere. The reason for this situation lies in the ontological manifestation that the law strength as it is. The latter is characterized as its transcendental property. There is no equality of parties (in fact, not legal) where always possible to manifest law strength like one contractor against the other. However, it is mentioned that the principle of legal equality has positive potential, which finds its expression in providing equal starting opportunities for all. In addition it is given the analysis of legal principles as freedom and justice. The attention pays to both negative and positive aspects of these principles. Based on this conclusion on the historically volatile content of these principles, implementation of which in public practice is determined by the actual order.